Postbiotic effects elicited by heat-inactivated Lacticaseibacillus rhamnosus GG against cow’s milk allergy in human cells - Oglio, Franca; Paparo, Lorella; Carucci, Laura; Gaeta, Alessia; Armiento, Samantha; Coppola, Serena; Molinaro, Antonio; De Castro, Cristina; Masino, Antonio; Mauriello, Vittoria; Michelini, Marco; Cozzolino, Marica; et al. (Frontiers in Immunology, 2026)
BackgroundThe probiotic L. rhamnosus GG (LGG) elicits immunomodulatory actions facilitating the immune tolerance acquisition in children with cow’s milk allergy (CMA). Emerging data suggest that heat-inactivated LGG postbiotic (LGGp) could improve gut health and immune function. We investigated the tolerogenic actions elicited by LGGp against CMA in human cells.MethodsPeripheral blood mononuclear cells (PBMCs) collected from IgE-mediated CMA children (n=6, all Caucasian, mean age 31.2 months) were stimulated with beta-lactoglobulin (BLG) in the absence or presence of LGGp. Activated regulatory T cells (Tregs)number was assessed by flowcytometry. Growth factors and cytokines modulating interleukins (IL) production were assessed by RT-PCR. IL-4, 5, 13 and 10 production was assessed by ELISA. The LGGp effects on gut barrier were evaluated using a Caco-2 cells-based experimental model by measuring transepithelial electrical resistance (TEER); tight junction proteins, Mucin-2 (Muc-2), and lactase expression; and FITC dextran permeability,ResultsLGGp exposure resulted in Tregs activation and beneficial modulation of cytokines production in PBMCs from CMA patients. These effects paralleled with beneficial effects on all biomarkers of gut barrier integrity.ConclusionsOur data suggest that LGGp, modulating several immune tolerance mechanisms, could be a promising therapeutic strategy against CMA.